2015
DOI: 10.18632/oncotarget.3347
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy induction by leptin contributes to suppression of apoptosis in cancer cells and xenograft model: Involvement of p53/FoxO3A axis

Abstract: Leptin, a hormone mainly produced from adipose tissue, has been shown to induce proliferation of cancer cells. However, the molecular mechanisms underlying leptin-induced tumor progression have not been clearly elucidated. In the present study, we investigated the role of autophagy in leptin-induced cancer cell proliferation using human hepatoma (HepG2) and breast cancer cells (MCF-7), and tumor growth in a xenograft model. Herein, we showed that leptin treatment caused autophagy induction as assessed by incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 60 publications
1
72
0
1
Order By: Relevance
“…In agreement, it has been shown that the anti-proliferative effects of APN in cancer cells occur through the AMPK-FOXO3 pathway Nepal and Park, 2013). APN promotes autophagy in macrophages by suppressing the AKT-mediated phosphorylation of FOXO3 , while leptin treatment activates the autophagic process via the p53-FOXO3 axis, playing a critical role in restricting tumour growth (Nepal et al, 2015). Moreover, leptin administration Table 1 List of human homologues and orthologues of lipid-metabolic genes identified as DAF-16 and/or TCER-1 targets through RNA-Seq by Amrit et al (2016) (Amrit et al, 2016) and their potential functions in lipid metabolism.…”
Section: Adipokinesmentioning
confidence: 66%
See 1 more Smart Citation
“…In agreement, it has been shown that the anti-proliferative effects of APN in cancer cells occur through the AMPK-FOXO3 pathway Nepal and Park, 2013). APN promotes autophagy in macrophages by suppressing the AKT-mediated phosphorylation of FOXO3 , while leptin treatment activates the autophagic process via the p53-FOXO3 axis, playing a critical role in restricting tumour growth (Nepal et al, 2015). Moreover, leptin administration Table 1 List of human homologues and orthologues of lipid-metabolic genes identified as DAF-16 and/or TCER-1 targets through RNA-Seq by Amrit et al (2016) (Amrit et al, 2016) and their potential functions in lipid metabolism.…”
Section: Adipokinesmentioning
confidence: 66%
“…also increases FOXO3 expression and the expression of genes related with autophagy (Nepal et al, 2015). However, it has also been documented that leptin administration inactivates FOXO3 in muscle cells (Sainz et al, 2009).…”
Section: Acdh-11mentioning
confidence: 95%
“…P53 operates within a broader regulatory network to define autophagic control [152][153][154][155][156][157]. When cells are subjected to oncogenic activation or genotoxic stress and P53 is activated, P53 is shown to induce autophagy [152,153].…”
Section: Other Important Transcription Factors Of Autophagy Regulatiomentioning
confidence: 99%
“…In this report, leptin-induced autophagy activation also contributes to the suppression of apoptosis of cancer cells, indicating that autophagy activation would be one of the survival mechanisms in hepatic cancer cells. 35) In conjunction with the results from adiponectin, autophagy induction would be a promising target for the modulation of cancer cell survival by adipokines.…”
Section: Effects Of Leptin On Proliferation Of Hepatic Cancer Cellsmentioning
confidence: 99%